Correlation between Cyclin Dependent Kinases and Artemisinin-Induced Dormancy in Plasmodium falciparum In Vitro. - Karen-Ann Gray (PLoS ONE, 2016)
Artemisinin-induced dormancy provides a plausible explanation for recrudescence following artemisinin monotherapy. This phenomenon shares similarities with cell cycle arrest where cyclin dependent kinases (CDKs) and cyclins play an important role.Transcription profiles of Plasmodium falciparum CDKs and cyclins before and after dihydroartemisinin (DHA) treatment in three parasite lines, and the effect of CDK inhibitors on parasite recovery from DHA-induced dormancy were investigated.After DHA treatment, parasites enter a dormancy phase followed by a recovery phase. During the dormancy phase parasites up-regulate pfcrk1, pfcrk4, pfcyc2 and pfcyc4, and down-regulate pfmrk, pfpk5, pfpk6, pfcrk3, pfcyc1 and pfcyc3. When entering the recovery phase parasites immediately up-regulate all CDK and cyclin genes. Three CDK inhibitors, olomoucine, WR636638 and roscovitine, produced distinct effects on different phases of DHA-induced dormancy, blocking parasites recovery.The up-regulation of PfCRK1 and PfCRK4, and down regulation of other CDKs and cyclins correlate with parasite survival in the dormant state. Changes in CDK expression are likely to negatively regulate parasite progression from G1 to S phase. These findings provide new insights into the mechanism of artemisinin-induced dormancy and cell cycle regulation of P. falciparum, opening new opportunities for preventing recrudescence following artemisinin treatment.